Students' Critical Thinking Skills and Sustainability Awareness in Science Learning for Implementation Education for Sustainable Development - Ekamilasari, Ekamilasari; Pursitasari, Indarini Dwi (Universitas Pendidikan Indonesia (UPI), 2021)
Quality and competent human resources are needed in the 21st century. Based on the importance of critical thinking skills and sustainability awareness and ESD implementation, it is necessary to study critical thinking skills and sustainability awareness, as well as the need for teaching materials and ESD implementation. The main novelties in this study are acquiring critical thinking skills and sustainability awareness, as well as the need for teaching materials and the implementation of ESD in this study are expected to be a consideration in preparing teaching materials that can train students to think critically and have sustainability awareness to support ESD implementation. The method used is descriptive. The data is processed quantitatively and interpreted qualitatively. The study was conducted on 213 students and six junior high school teachers in the city of Bogor. The level of critical thinking skills of students is in the low category.. The total mean of 3.65 indicates that the level of sustainability awareness of students is a moderate level. The implementation of ESD is important to overcome various environmental problems that are currently occurring. ESD learning is expected to increase students' sustainability awareness and critical thinking skills. This study are expected to be a consideration in preparing teaching materials that can train students to think critically and have sustainability awareness to support ESD implementation.